THE INFLUENCE OF INFORMATION ASYMMETRY, SIZE, AND FINANCIAL RATIOS ON EARNING MANAGEMENT TOWARDS BANKING SECTOR - Anugerah Adhi Prasetyo (Universitas Gunadarma, 2017)
The purpose of this research is to investigate the influence of user participation on accounting information system performance with top management support, task complexity, system complexity, user skill as moderating variable and the effect of accounting information system performance on individual performance. The population in this study are employees on good banking company bank Persero or BUSN Devisa listed in Bank Indonesia totaling 39 banks including bank persero 4 and 35 BUSN Devisa. Total Bank to be sampled are 8 banks and total of respondent are 100 respondents. Using the Structural Equation Modelling (SEM) and Moderate-Structural Equation Modelling. The results show that user participation influence significantly on AIS performance. Top management support, task complexity, system complexity, user skill moderates the effect of user participation on AIS performance. And AIS performance influence significantly on individual performance Keywords: Infromation Asymmetry, Size, Return on Asset, Capital Adequacy Ratio, Loan to Deposit Ratio, Earning Management